现代性的问题及处方:涂尔干主义的历史效果 - 谢立中 (社会学研究, 2003)
The word “Durkheimism” in this paper refers to the set of proposals put forward by Emile Durkheim concerning the ways out of the economic, social and spiritual crises he saw in his time. Those proposals were not just arguments on paper,but, in fact, an important component of social reforms in western developed countries of the 20 th century. The aim of this article is to show that those proposals of Durkheimism had indeed brought some positive contributions to the alleviation of those crises faced by the liberal modernity institution in the end of the 19 th century, but they also had produced some unexpected harmful side effects which we must give serious consideration when we apply them to our own situation.
Keywords: 涂尔干; 社会伙伴关系; 发达资本主义国家; 社团主义; 劳资双方; 联邦德国; 西方发达国家; 现代性; 工资增长率; 现代社会